Responsible investment and ESG: an economic geography - Harnett, E (2018)
There is a growing awareness of, and commitment to, Responsible Investment (RI) in the institutional investment markets internationally. RI is defined as the consideration of environmental, social and/or governance (ESG) issues in long-term oriented investment decision-making. As the role of ESG in determining investment risk and opportunity becomes more evident, and as ESG data becomes more available, RI is increasingly seen as an area of potential investment innovation. This thesis applies institutional, evolutionary and relational economic geography theories to examine this trend, exploring the mainstreaming of RI through novel empirical and conceptual research. This thesis examines the investment learning processes and information channels available in Western liberal market economies of the UK, US and Australia. It adopts economic geography knowledge and innovation frames towards answering the question: 'Now that ESG information is more widely available in the investment markets, why has this not catalysed a greater shift towards RI integration in mainstream investment decisions?'. Learning, language and leadership factors within the institutional investment industry are all argued to help answer this question. This research uses a mixed method approach, with analysis based on a survey of 154 investment professions, 97 semi-structured interviews and a case of RI innovation. This thesis develops a conceptual framework of the communication channels and information sources used in investors' innovation-decision-process, drawing attention to the importance of both social and asocial learning processes in generating and sharing knowledge about climate issues within investment markets. Following this, the thesis examines the role of 'local buzz' and 'global pipelines' in facilitating access to, and uptake of, ESG information. Levels of buzz and pipelines are found to vary in different financial centres, and are facilitated by formal and informal networking linked to RI groups. Importantly, then, this thesis finds that both spatial and relational proximity influence investors’ access to ESG information and RI knowledge. The second half of this thesis examines whether and how RI information, knowledge and practice can be integrated into existing individual and organisational decision-making frameworks. It highlights the need to better translate RI information into investment-relevant language, and provides an example of how environmentally-driven stranded assets can be reframed as a version of sunk costs, contributing novel spatial-temporal theorisations of this concept. Through an illustration of RI decision-making by the investment consultant Mercer and the University of Sydney endowment fund, this thesis highlights that the capacity to integrate RI through the investment chain does exist. However, willingness to do so is found to be hindered by institutional and organisational path dependent norms, reduced only in some firms by seeing RI as an innovative area of competitive advantage from growing client demand. This thesis therefore finds that RI is being adopted in increasingly more mainstream investment firms, but this is not always fully integrated throughout the firm, and that uptake is geographically varied based on exposure to networks of information and knowledge sharing, and institutional, organisational and individual norms. Ultimately, this thesis therefore contributes towards understandings of the processes underpinning the mainstreaming of RI, but also contributes to broader economic geographies of investment, knowledge sharing and innovation.